Analisis Beban Kerja pada Lini Produksi Menggunakan Metode Cardiovascular Load dan Work Load Analysis - Hidayati, Evi; Purnama, Jaka (SURYA TEKNIKA, 2026)
The study was conducted at PT XYZ, a manufacturing company engaged in the production of yarn using a make-to-stock production system. The problem faced by the company is the failure to achieve consistent production due to suspected imbalances in operator workloads at several workstations. This study aims to analyze operator workload levels and determine optimal workforce requirements using the Cardiovascular Load (CVL) and Work Load Analysis (WLA) methods. The CVL method was used to determine the workload levels experienced by operators, derived from work heart rate and resting heart rate, while WLA was used to calculate the optimal number of operators based on working time. Research data was obtained through direct observation, work time measurements, and measurements of operators’ heart rates during the production process. The results indicate the presence of operators with high workload levels as well as an imbalance in the number of workers at several workstations, resulting in the production process not yet operating optimally. Therefore, adjustments to the number of workers and a more balanced division of labor are necessary to improve the company’s productivity.